Paweł Churski, Waldemar Ratajczak (red.) Regional development and regional policy in Poland: First experiences and new challenges of the European Union membership. Studia Regionalia, vol. 27, part I, II. Polish Academy of Sciences - Czasopisma, Redakcja (Rozwój Regionalny i Polityka Regionalna, 2010)
Paweł Churski, Waldemar Ratajczak (red.) Regional development and regional policy in Poland: First experiences and new challenges of the European Union membership. Studia Regionalia, vol. 27, part I, II. Polish Academy of Sciences, Committee for Spatial Economy and Regional Planning, Warszawa 2010 Part I 296 ss. Part II 288 ss. ISBN 978-83-89693-28-0 (Part I) ISBN 978-83-89693-08-2 (Part II)